Detecting Intraspecific Character Displacement by Morphological Markers in Riverine-Dwelling Invertebrate Larvae: The Case Study of Head Shape Variability in Leuctra fusca (Plecoptera: Leuctridae) - Raffaella Bravi; Lorenzo Traversetti; Massimiliano Scalici (Journal of Basic & Applied Sciences, 2014)
Since morphological markers are recognized as useful tools to evaluate events of anthropic disturbances, we performed a preliminary study on head shape variability in the riverine-dwelling Leuctra fusca larvae as early alarm systems in running waters. Particularly, heads of 32 larvae were collected from two localities of River Aniene (central Italy) and photographed for digitizing landmarks and semilandmarks. The Cartesian x-y coordinates of all points were firstly converted to shape coordinates by Procrustes superimposition, and then analyzed for exploring the full potential of the application of geometric morphometric techniques. Where the principal component analysis revealed a clear pattern of variation between the 2 sampling sites, the Procrustes ANOVA highlighted this variation as highly associated with fluctuating asymmetry, the latter being traditionally connected with developmental accidents due to environmental conditions. No directional asymmetry was observed. Finally we didn’t find any pattern of allometric variation in the studied structure. Our study indicates that further studies ought to be employed to use geometric morphometrics as a valid tool for detecting and describing morphological variation as biomarkers in invertebrate organism such as stoneflies.